Pernambuco y la independencia: entre el federalismo y el unitarismo - Luiz Geraldo Silva (Nuevo mundo - Mundos Nuevos, 2013)
This article focuses on the formation of opposing political groups in the province of Pernambuco after the Portuguese constitutional revolution of the year of 1820. In first place, there were political groups attached to an autonomist perspective, a type of local federalist ideology. On the other hand, there were the political groups which supported the process of construction of the unitary State and, in consequence, got involved in the civil war which breaks out at the year of 1824. This article analyses the struggles between those groups from 1820 to 1824, the year of Ecuador Confederation movement, and also examines political practices and ideas of blacks and free colored men involved in this process.